Negro-White Unity - Winston, Henry (New Outlook Publishers, 32 Union Sq. E., New York, N.Y., 1967)
Pamphlet promoting racial equality, written by Henry Winston and published in February 1967. This pamphlet contains the text of a report presented to a meeting of the National Committee, CPUSA, December 6, 1966.
Negro-White Unity by Henry Winston, February 1967
Negro-White Unity by Henry Winston, February 1967, Book 22, Box: 1, Book: 22. Civil Rights Papers, MS-134.
Keywords: Civil Rights Movement, Representation, Henry Winston